Mengelola Perbedaan Menjadi Sebuah Kekayaan: Suatu Analisis Teks Kolose 3:12-17 - Manase Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
Success is making a difference in wealth is the longing of every human being in general and believers in particular. Everyone longs for unity. However, the reality of conflict often occurs both within the family, in the church, and in the life of the nation. One of the causes of conflict is due to not being able to manage differences. The differences in question are differences in religion, ethnicity, culture, education, and so on. If these differences are not managed properly, conflicts will continue to exist both within the family, in the church, and in the life of the nation. Seeing the situation as described above, a theory is needed on how to manage differences into wealth. This article will provide a theory on how to manage the differences to become wealthy. This theory is an analysis of Colossians 3: 12-17.